Examining the Relationships Between Childhood Exposure to Intimate Partner Violence, the Dark Tetrad of Personality, and Violence Perpetration in Adulthood - Plouffe, Rachel A. (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) is a major international public health concern that poses significant mental and physical health risks for affected individuals. To improve prevention efforts, it is imperative that researchers and government bodies understand risk factors for IPV. One such risk factor concerns the extent to which violence is intergenerational, such that exposure to violence predisposes individuals to engage in violence toward intimate partners. The purpose of this research is to assess childhood exposure to violence as a risk factor for perpetration of IPV in adulthood, and to evaluate the Dark Tetrad personality traits as mediators in this relationship. We recruited 153 men and 246 women (age range = 18?73, Mage = 33.50, SDage = 10.26) through Amazon?s Mechanical Turk to complete a series of questionnaires and an open-ended IPV perpetration assessment. Results showed no relationship between IPV perpetration and childhood IPV exposure, indicating that mediation analyses were not possible. Possible explanations are discussed. Follow-up exploratory analyses demonstrated that gender moderated the relationships between childhood IPV exposure and levels of Factor 1 psychopathy and Machiavellianism. Specifically, men who were exposed to IPV in childhood were more likely to develop higher levels of Factor 1 psychopathy and Machiavellianism, whereas women were not. Overall, our findings highlight the importance of providing researchers and clinicians with a greater understanding of environmental events preceding maladaptive trait development. It is also important for researchers and clinicians to consider gender differences in pathways between exposure to IPV and subsequent development of dark personality traits. Theoretical and practical implications are discussed.